The Interactive Effects of Affect Lability, Negative Urgency, and Sensation Seeking on Young Adult Problematic Drinking. (27th December 2012) - Karyadi, Kenny; Coskunpinar, Ayca; Dir, Allyson L.; Cyders, Melissa A.
Abstract : Prior studies have suggested that affect lability might reduce the risk for problematic drinking among sensation seekers by compensating for their deficiencies in emotional reactivity and among individuals high on negative urgency by disrupting stable negative emotions. Due to the high prevalence of college drinking, this study examined whether affect lability interacted with sensation seeking and negative urgency to influence college student problematic drinking. 414 college drinkers (mean age: 20, 77% female, and 74% Caucasian) from a US Midwestern University completed self-administered questionnaires online. Consistent with our hypotheses, our results indicated that the effects of sensation seeking and negative urgency on problematic drinking weakened at higher levels of affect lability. These findings emphasize the importance of considering specific emotional contexts in understanding how negative urgency and sensation seeking create risk for problematic drinking among college students. These findings might also help us better understand how to reduce problematic drinking among sensation seekers and individuals high on negative urgency.